The Practice of Community-Based Water Resource Management in Rural Indonesia - Rifqi Abdul Hafidh; Ida Widianingsih; Ahmad Buchari (Universitas Sultan Ageng Tirtayasa, 2021)
Although The government has issued various regulations and models of water resources governance at the local level, community-based water resources governance is needed in responding to challenges in water resource management. This paper discusses the case of water resources management in Srogol village (Cigombong sub-district, Bogor district) which applies a community-based water resources governance model known as Janggol. Culturally, Janggol has been deeply rooted in the social system in the Bogor area. Janggol in the upstream Cisadane watershed was appointed in 2018 to manage the water supplied to the community from the Ciwaluh spring. However, in practice the community-based management that is implemented is often wrong in its function and creates other quite complex problems. This research aims to analyze why the implementation of community-based water resource management in Srogol village is not optimal and what efforts must be made to encourage sustainable natural resource management using the concept of Community-based natural resource management. This research uses a qualitative approach, by extracting data using an interview process to predetermined stakeholders. Based on the research results, the water management carried out by Janggol is not optimal due to the lack of adaptation of managers in water management, the lack of community participation in water management, and the lack of knowledge of Janggol in providing services as an institution.